Irritability in Huntington's Disease: Factor Analysis of Snaith's Irritability Scale. Issue 3 (1st October 2016) - Maltby, John; Dale, Maria; Underwood, Mandy; Simpson, Jane; ,
Abstract: Background: Elevated levels of irritability are reported to occur in a number of neurological conditions, including Huntington's disease (HD), a genetic neurodegenerative disorder. Snaith's Irritability Scale (SIS) is used within HD research, but no psychometric evaluation of this instrument has previously been undertaken. Therefore, the current study aimed to analyze the factor structure of this scale among an HD population. Methods: Exploratory and confirmatory factor analysis were used to examine the structural properties of SIS using responses from 1, 264 HD gene expansion carriers, across 15 European countries, who were engaged in the REGISTRY 3 study. Results: An exploratory factor analysis of a subsample of the data suggested a two‐factor interpretation of the data comprising "temper" and "self‐harm." Eight possible models were tested for goodness of fit using confirmatory factor analysis. Two bifactor models, testing general and group factors in the structure of the scale, provided an equivocal "good" fit to the data. The first comprised a general irritability factor and two group factors (as originally proposed using SIS): outward irritability and inward irritability. The second comprised a general irritability factor and two group factors (as proposed by the exploratory factor analysis): temper and self‐harm. The findings from both models suggested that the loadings of items were higher on the general factor. Conclusions: Bifactor models are proposed to best consider the structure of the SIS, with findings suggesting that an overall score should be used to measure irritability within HD populations.